The image of Spain abroad from 2008 to 2012: El largo camino hacia la marca paraguas - Rodríguez Gómez, Alfredo A. (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
The image of Spain abroad is of the utmost importance for its politics in general and for establishing its hallmarks outside its borders. This paper analyzes the crisis it had in the global economic crisis of 2008 and following years through two Anglo-Saxon media and determines the importance of communication in public diplomacy and the need it had to achieve true country brand strategies to overcome the crisis. image bump that, to a greater or lesser extent caused by third parties, had at that time.